Writing Development in Struggling Learners Understanding the Needs of Writers across the Lifecourse - Miller, Brett; McCardle, Peggy; Connelly, Vince (Studies in Writing, 2017)
In Writing Development in Struggling Learners, international researchers provide insights into the development of writing skills from early writing and spelling development through to composition, the reasons individuals struggle to acquire proficient writing skills and how to help these learners.; Readership: Academic libraries, graduate students; post-graduate researchers; literacy researchers; educated lay persons; literacy specialists; primary/secondary educators.